2011
DOI: 10.1071/pc110068
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and habitat preferences of co-occurring vertebrate species: Case study of an endangered frog and an introduced toad in Fiji.

Abstract: Wildlife management, particularly the conservation of threatened species, often involves habitat management and an understanding of species preferences. Much ecological data used to establish rare and endangered species distributions and/or habitat associations exists in the form of point counts which often violates the assumptions of commonly used statistical techniques. In this study, the spatial distribution and habitat preferences of an endangered, endemic frog (Platymantis vitianus — Fiji ground frog) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Seeking refuge following a stressful encounter could be beneficial if the intruder is a visual hunter, but may prove detrimental when the predator is able to enter these substrates. There is empirical evidence that the spatial distributions of the cane toads and Fijian ground frogs on Viwa Island overlap quite significantly [31]. We studied the male ground frogs during breeding thus future studies should investigate whether responses (fearfulness and corticosterone responses) of male frogs are similar outside the breeding season, including their correlation with testosterone [53,54] and body condition [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeking refuge following a stressful encounter could be beneficial if the intruder is a visual hunter, but may prove detrimental when the predator is able to enter these substrates. There is empirical evidence that the spatial distributions of the cane toads and Fijian ground frogs on Viwa Island overlap quite significantly [31]. We studied the male ground frogs during breeding thus future studies should investigate whether responses (fearfulness and corticosterone responses) of male frogs are similar outside the breeding season, including their correlation with testosterone [53,54] and body condition [7].…”
Section: Discussionmentioning
confidence: 99%
“…The endemic ground frog population on Viwa Island are preyed upon by the cane toad ( Rhinellamarina ) [3133]. Evidence dating back 20 years highlights that cane toads predate upon froglets and juveniles [34].…”
Section: Introductionmentioning
confidence: 99%
“…The stocking density of one adult ground frog to four adult cane toads was based on previously reported abundance estimates for the natural habitat on Viwa Island that the enclosures were built upon (Thomas et al . ). Control enclosures were only stocked with 100 adult ground frogs (50 adult male and 50 adult females).…”
Section: Methodsmentioning
confidence: 97%
“…By using different vegetation communities that influenced habitat choice and hence densities of toads and ground frogs across our study site, it was possible to assess physiological data from ground frogs at naturally occurring high and low cane toad densities (Thomas et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…In Arroyo Hornitos there were no records of L, forreri and L. melanonotus, although these species were generally observed in low numbers at other streams during the study. Some studies have reported that these two species are clearly associated with disturbed or open habitats, and with water bodies that have long, stable hydroperiods (Carrasco, 1989;Ford & Scott, 2006;Suazo-Ortuño et al, 2008;Urbina-Cardona, Olivares-Pérez, & Reynoso, 2006;Thomas, Morrison, Winder, & Morley, 2011;Mendenhall et al, 2014). Therefore, it may be that the conserved, seasonally dry forest of Chamela is not an adequate habitat for this species to occur in high numbers.…”
Section: Discussionmentioning
confidence: 96%